Rheological behaviour of NiO/YSZ slurries for drying-free casting - Horri, B.; Dong, Dehua; Selomulya, C.; Wang, H. (Elsevier, 2012)
We have recently developed a new drying-free casting method for shape forming of ceramics, in which a polymerizable solvent such as furfuryl alcohol (FA) is used to disperse the ceramic powders, and then polymerized into a poly (furfuryl alcohol) (PFA) binder during the casting process. Compared with conventional casting processes, this method offers more flexibility in controlling the microstructure of ceramics and eliminates defects that are likely to arise from the drying step. Controlling the rheological behaviour of ceramic slurries is an important step in the casting process to achieve improved microstructural properties. In this study, the viscosity of slurries comprising NiO/YSZ (yttria stabilized zirconia) powders and FA as solvent was investigated over a wide range of shear rates (1 s−1–1000 s−1) and at different volumetric solid concentrations (from 20% to 70%), while the effects of dispersant were quantified by adding different amounts of PVP (polyvinyl pyrrolidone) between 1 wt.% and 4 wt.%. The minimum viscosity of NiO/YSZ/FA slurries could be achieved with 2 wt.% dispersant. The experimental data relating the changes in viscosity to the volumetric solid concentration were modeled using different viscosity models, with Liu's equation showing the best fit for NiO/YSZ/FA slurries with and without dispersant. The slurries showed a highly pseudoplastic behaviour without dispersant, while adding PVP as dispersant effectively modified the rheological behaviour toward Newtonian fluids.